Spectrophotometric Assessment of Heme Oxygenase-1 Activity in Leishmania-infected Macrophages - Basu, Moumita (Bio Protoc, 2020)
Heme oxygenase-1 (HO-1) is a stress responsive enzyme that metabolizes heme and releases free iron, carbon monoxide (CO), and biliverdin (BV), which rapidly undergoes conversion to bilirubin (BL). Estimation of bilirubin is the basis of HO-1 assay. HO-1 activity is widely employed to determine antioxidant response of cells under different physiological stress environment. Intra-macrophage infection often acts as such a stress inducer and measurement of HO-1 activity in infected cells indicates the ability of pathogens towards modulating oxidative response of host. The present protocol describes analysis of HO-1 activity in infected macrophages by spectrophotometric method, which is much less complex and therefore advantageous over other methods like high-performance liquid chromatography, radiochemical methods and detection of CO by gas chromatography. The main steps include: (1) Preparation of macrophage microsomal fraction containing HO-1 (2) Isolation of rat liver cytosolic fraction containing biliverdin reductase and (3) Assessment of heme oxygenase-1 activity by spectrophotometric detection of bilirubin. This method provides a simple and sensitive approach to measure cellular antioxidant response under infected condition.